Designing an improved structure of the tool for repairing the brake pipe connectors in vehicles - Gnitko , Sergiy; Vasyliev, Ievgen; Popov , Stanislav (Eastern-European Journal of Enterprise Technologies, 2021)
This paper addresses the issue of difficulties in servicing the brake pipe connectors for passenger cars, the service life of which exceeds 8‒10 years, which is associated with the deteriorated loosening of connectors. The existing ways to loosen the connectors of brake pipes have been investigated, especially those whose dismantling is complicated due to the corrosion and contamination of mated surfaces as a result of their wetting when driving a car. A conventional structure of the connector has been analyzed, which is installed in that place of the car that is the most unprotected from moisture and dirt – on the brake cylinder. The conditions that do not contribute to its failure-free loosening have been examined. The design of a specialized split clamping ring wrench has been considered, which can transmit the greatest value of the torque to the connector when loosening it; sometimes, however, its predefined value would not suffice. A computer-based finite-element simulation was employed to derive the models of the deformation state for the node «connector ‒ wrench». Based on the analysis of the models of different deformation state of a specialized split clamping ring wrench, the required profile of the geometrically balanced locked hexagonal profile of the wrench was defined. The analysis of the efficiency of the tightening and loosening level is determined by comparing the numerical values of the torque, which is applied to the connectors of the brake pipes. The torque values are measured by a specially devised technique. The introduction of the developed measurement technique makes it possible to compare the efficiency of wrenches of different designs by analyzing the maximum values of torques, which the wrenches can transmit to the connectors. Taking into consideration the identified shortcomings in the structure of the brake pipe connectors, the shape of the connector has been designed that is free from the specified drawbacks. The new structure provides for the possibility of using a conventional carob wrench for loosening when the mated surfaces are exposed to contamination and corrosion